Sequencing Games with Slack Due Windows and Group Technology Considerations. Issue 2 (February 2017) - Ji, Min; Liu, Sai; Zhang, Xiaolin; Cao, Keke; Cheng, T.
Abstract We study sequencing situations in which the customers are initially sequenced to be served by a single server. We consider both slack due windows and group technology simultaneously. We introduce two division rules to divide among the customers the cost saving from resequencing the customers to follow the optimal sequence and characterize the rules axiomatically. Applying cooperative game theory to analyze the sequencing games corresponding to the sequencing situations, we use the theory's solution concepts to solve the games.